1, 3-Bis(pyren-1-yliminomethyl)calix[4]arene as a selective fluorescent turn-on sensor for mercury(II) ion. Issue 3 (4th March 2018) - Tanaka, Shinya; Hirasawa, Kengo; Watanabe, Kyohei; Hattori, Tetsutaro
Abstract: A novel calixarene-based diimine, 1, 3-bis(pyren-1-yliminomethyl)calix[4]arene (5 ), serves as a turn-on-type fluorescent sensor, which selectively detects Hg 2+ in THF/H2 O (99:1, v/v) in the presence of various other metal ions. Such selectivity is not seen with half salen1 derived from salicylaldehyde and 1-aminopyrene. 1 H NMR analysis reveals that it is a chemodosimetric sensor based on its hydrolysis mediated by Hg 2+ to release 1-aminopyrene molecules as fluorescent chromophores. Abstract :